1984
DOI: 10.1111/j.2044-8279.1984.tb02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Causal Attributions for Expected and Actual Examination Outcome: A Study of the Expectancy Confirmation and Egotism Models

Abstract: The expectancy confirmation and egotism models of causal attributions for success and failure were investigated with 400 fifth form students taking the New Zealand School Certificate English examination. Attributions for expected exam outcome and actual exam outcome were assessed with a scale containing 33 items categorised into the attribution dimensions of stability and locus of causality. The results suggested that exam outcome attributions are a function of both expectancy confirmation and valence of actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Although students from high decile schools have the highest rates of NCEA achievement according to the NZQA data mentioned earlier, they are also more likely to have higher expectations of their teachers, as hypothesised by Ali et al (2005). This hypothesis is further substantiated by Chapman and Lawes (1984) as mentioned in the introduction, when they suggest that low achieving or failure-prone individuals have reported the tendency for success to be seen as externally caused and failure as internally caused (1984). High decile students may therefore be more likely to see success as being internally caused and failure to be externally caused.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Although students from high decile schools have the highest rates of NCEA achievement according to the NZQA data mentioned earlier, they are also more likely to have higher expectations of their teachers, as hypothesised by Ali et al (2005). This hypothesis is further substantiated by Chapman and Lawes (1984) as mentioned in the introduction, when they suggest that low achieving or failure-prone individuals have reported the tendency for success to be seen as externally caused and failure as internally caused (1984). High decile students may therefore be more likely to see success as being internally caused and failure to be externally caused.…”
Section: Resultsmentioning
confidence: 87%
“…According to New Zealand Qualifications Authority (NZQA) released data from 2005 to 2007, at levels one, two and three, students at high decile schools acquire NCEA at a much higher rate than students at mid-decile schools, who acquire it at a much higher rate than students at low decile schools (NZQA, 2009). Students from low decile schools have lower rates of success in obtaining NCEA, and if the findings of Chapman and Lawes (1984) are correct, are more likely to attribute less than expected performance to themselves as opposed to the teacher. Conversely, students from high decile schools may have higher expectations that their education will be of a higher quality, but be more likely to attribute less-than-expected academic performance to their teacher.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While exam-related attribution studies have been reported, most have used structured measures of attributions containing a restricted number of causes (Feather and Simon, 1973;Bar-Tal and Darom, 1979; Davis and Stephan, 1980;McMillan and Spratt, 1980;Chapman and Lawes, 1984 (Frieze, 1976;Frieze and Snyder, 1980), tests in general rather than specifically (Frieze, 1981; Bar-Tal et al, 1984), or have referred to attributions made by children or teachers about other children (Cooper and Burger, 1980;Little, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Causal attributions have been studied in terms of achievement-related activities (Chapman & Lawes, 1984;Chapman & Lawes, 1987;Perry & Penner, 1990;Weiner, 1986), psychopathology (Brewin, 1988, l989), health issues (Grossman, Brink & Hauser, 1987;Major, Mueller & Hildebrandt, 1985;Taylor, Lightman & Wood, 1984), marital interactions (Bradley & Fincham, 1990), criminal blame (Gudjonsson & Petursson, 1991 ;Loza, 1993) and criminal responsibility (Howe & Loftus, 1992;Levett & Kuhn, 1991). Self-attributions have been linked to expectancies, affect and future behaviour in a variety o f situations (Rrewin, 1988;Heider, 1958;Weiner, 1986).…”
mentioning
confidence: 99%